Peningkatan Kemampuan Public Speaking bagi Pelajar SMA Yuppentek Kota Tangerang - Dewi Arlusi, Rosalia; Afgiansyah; Octory, Gadis (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service (PkM) program aimed to address the low public speaking skills among senior high school students in Tangerang City. The gap between students’ competencies and industry demands required adaptive, participatory training. The program was implemented at SMA Yuppentek Tangerang using service learning and participatory action research (PAR) through training, group discussions, and simulations. A total of 85 students, supervising teachers, and external partners were actively involved. Pre–post test results indicated significant improvements in understanding communication concepts, MC and moderator roles, and public speaking practice. Students reported increased self-confidence and skills in delivering ideas to an audience. The activity also strengthened collaborative networks between schools, lecturers, teachers, and local stakeholders. This PkM not only enhanced knowledge but also provided practical skills relevant to the workforce, supported University Key Performance Indicators (IKU 3 and IKU 7), and aligned with the Merdeka Belajar–Kampus Merdeka (MBKM) policy. By using experiential learning and stakeholder engagement, the program contributes to shaping a confident, communicative, and adaptive young generation prepared for future challenges.